Q: What is the Z2?

Write your answer...

Submit

Still have questions?

Related questions

0

its either (z2+ 9)(z - 2) , (z2+ 2)(z - 9) , or (z2- 9)(z - 2)

After all forces are summed with vector addition, the result is usually known as the net force (Fn) and can be used in the formula (Fn = ma).

z2 + 9z + 18 = z2 + 6z + 3z + 18 = z(z+6) + 3(z+6) = (z+6)*(z+3)

x= z2 - 3

Any pi network can be transformed to an equivalent T network. This is also known as the Wye-Delta transformation, which is the terminology used in power distribution and electrical engineering. The pi is equivalent to the Delta and the T is equivalent to the Wye (or Star) form. Pi NetworkT Network The impedances of the pi network (Za, Zb, and Zc) can be found from the impedances of the T network with the following equations: Za = ( (Z1*Z2)+(Z1*Z3)+(Z2*Z3) ) / Z2 Zb = ( (Z1*Z2)+(Z1*Z3)+(Z2*Z3) ) / Z1 Zc = ( (Z1*Z2)+(Z1*Z3)+(Z2*Z3) ) / Z3

z1,z2,

If z1=a+ib and z2=c+id then the product z1*z2=(ac-bd)+i(ad+bc)

Sony Xperia Z2 lets you display 4K footage on your 4K TV .Galaxy S5 has fingerprint scanner and heart-rate monitor. micro sd card on Z2 up to 16GO, Galaxy S5 up to 128Go Camera Z2 20.7 megapixel, Camera S5 16 megapixels USB port 2.0 on Z2, USB port 3.0 on S5 No Tuner FM (Radio)on S5 and Yes on Z2 Screen IPS with Triluminos on Z2, Super AMOLED on S5 better if you need big storage then Galaxy S5, other depends on how you want to use your phone then decide one or the other

ax * ay = a(x+y) Example: z2 * z3 = z5 (ax)y = axyExample: (z2)3 = z6 ax/ay = a(x-y) Example: z3/z2 = z1 = z

An equilateral triangle is always inscribed in a circle.This means that if you can prove that z1, z2 and z3 are the vertices of an equilateral triangle, they automatically lie on a circle subscribing it.Compute |z1-z2|, |z1-z3| and |z2-z3|. These need to be equal for z1, z2 and z3 to lie on an equilateral triangle. If not, they aren't lying on an equilateral triangle.for z=a+ib, |z| = (a^2+b^2)^(1/2).To find the center c of the circle, note that (z1-c)+(z2-c)+(z3-c) = 0, hence,c = (z1+z2+z3)/3.

z2